A probable anthropic origin of Nerium oleander L. (Apocynaceae) population in Montecristo island (Italy, Tuscany): evidence from loci polymorphism and ISSR analysis. Issue 1 (2nd January 2018) - Lazzaro, Lorenzo; Sarracco, Eleonora; Benesperi, Renato; Coppi, Andrea
Abstract: Nerium oleander (hereafter oleander) is a Mediterranean evergreen shrub representing the only species in the genus Nerium (Apocynaceae) . Oleander is widespread across the entire Mediterranean basin both as spontaneous native plant and as ornamental cultivated plant. Concerns regarding the native origin of oleander populations may arise particularly in case of ecosystem restoration interventions, when the introduction of alien species or populations should be avoided. Within this work we evaluate the origin of oleander population on the Island of Montecristo (Central Italy), aiming to provide useful information for the implementation of conservation actions on the Island. We used ISSR markers to assess its native or feralized origin by comparison with two reference populations. Our results indicate a probable anthropic origin for the population of Montecristo, which share several characters close to the anthropic reference population, such as a relatively high polymorphism detected and a close ISSR profile.